If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 * 2x + -4(3x + 1) = -27 Multiply 3 * 2 6x + -4(3x + 1) = -27 Reorder the terms: 6x + -4(1 + 3x) = -27 6x + (1 * -4 + 3x * -4) = -27 6x + (-4 + -12x) = -27 Reorder the terms: -4 + 6x + -12x = -27 Combine like terms: 6x + -12x = -6x -4 + -6x = -27 Solving -4 + -6x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -6x = -27 + 4 Combine like terms: -4 + 4 = 0 0 + -6x = -27 + 4 -6x = -27 + 4 Combine like terms: -27 + 4 = -23 -6x = -23 Divide each side by '-6'. x = 3.833333333 Simplifying x = 3.833333333
| 5/9x=20 | | 4y+2=9y+8 | | 4x-9=6x+c | | 2x^2+18x-7=0 | | 107-4x=23x+17 | | 0.5+2=8+x | | (3x-4)-(2x-2)= | | -8b-7-2b= | | (3+3b)*(2+3b)= | | 7-(1+x)-12y= | | 10+(h-1)(2)=22 | | -x-46=2(2x-3) | | (x-3)+(3x+5)= | | 6x+20=86 | | 4(3x-5)=-32 | | 4x-8=2(x-2) | | 3(3x+1)=x-5 | | 2x+16=5(3x-2) | | 95-4x=14x+17 | | -7x(x)+x+5=0 | | 2x^2-30x+45=0 | | a=10+20d | | a=20d+10 | | 42=7x(2x) | | 34=5.2x | | 9-7x=173-35x | | 3/x+1-2/x=7 | | 2(x+5)=5(x-2) | | 3x+12=68x-5x | | 2(x+5)=5(x+2)-3x | | 8x+3=2x+9 | | -4ln(1)=0 |